1997
DOI: 10.1097/00007632-199705010-00011
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Success From a Multidisciplinary Treatment Program for Chronic Low Back Pain

Abstract: This study has demonstrated that the most important variable in determining a successful treatment of chronic low back pain is the reduction of subjective feelings of disability in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
0
27

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(141 citation statements)
references
References 59 publications
10
104
0
27
Order By: Relevance
“…Hildebrandt et al 37 studied patients with low-back pain and demonstrated that a negative self-evaluation for predicting a return to work was related to a longer period out of work and an application for pension was significantly related to a low probability of a patient's return to work. Although this result was statistically insignificant, the authors also stated that patients with a low level of education or low professional status were less likely to return to work, a statement confirmed by other studies 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Hildebrandt et al 37 studied patients with low-back pain and demonstrated that a negative self-evaluation for predicting a return to work was related to a longer period out of work and an application for pension was significantly related to a low probability of a patient's return to work. Although this result was statistically insignificant, the authors also stated that patients with a low level of education or low professional status were less likely to return to work, a statement confirmed by other studies 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Developed in 1983, this rehabilitation program is a variant of chronic pain management based on the biopsychosocial model of pain and disability, and is specifically intended for rehabilitation of compensation injuries (Mayer et al, 1985). The efficacy of functional restoration for CDOMD, as well as the objective outcomes for treatment monitoring, have been extensively reviewed in the literature (Bendix et al, 1996;Hildebrandt, Pfingsten, Saur, & Jansen, 1997;Jousset et al, 2004;Mayer et al, 1998;Mayer et al, 1985;Mayer et al, 1987;Rainville, Kim, & Katz, 2007;Wright, Mayer, & Gatchel, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Objective oneyear post-rehabilitation outcomes have been obtained from cohort studies, as well as RCTs, and include: increased resumption of active occupational status and activities of daily living; decreased health care utilization; reduced levels of pain intensity; improved readiness to change; improved psychological well being; and, resolution of outstanding medico-legal issues (Becker, Sjogren, Beck, Olsen, & Eriksen, 2000;Guzman et al, 2001;Hazard et al, 1989;Mayer et al, 1985;Patrick, Altmaier, & Found, 2004). The highly satisfactory results of functional restoration have been shown to be temporally stable (Mayer et al, 1987), and can be generalized across different socioeconomic and medico-legal systems (Bendix et al, 1996;Corey, Koepfler, Etlin, & Day, 1996;Hildebrandt, Pfingsten, Saur, & Jansen, 1997;Jousset et al, 2004). Finally, it has been demonstrated that functional restoration, along with other interdisciplinary approaches to pain management, are more cost-effective than standard conservative treatment (Gatchel & Okifuji, 2006;Skouen, Grasdal, Haldorsen, & Ursin, 2002;Turk, 2002;Turk & Okifuji, 1997).…”
Section: Tertiary Carementioning
confidence: 99%
See 1 more Smart Citation
“…Studien konnte gezeigt werden, dass eine verbesserte körperli che Funktionsfähigkeit aufgrund der MMT, affektiver Distress, geringere Abwesenheiten vom Arbeitsplatz sowie die Intensität der Inanspruchnahme medizinischer Leistungen vor Initiierung der MMT mit der Schmerzintensität nach der MMT assoziiert sind. [17][18][19]. Bezüglich der Patienten, die eine MMT erhielten und einen un günstigen Kostenverlauf aufwiesen, ist zu beachten, dass der un günstige Kostenverlauf nicht notwendigerweise darauf hinwei sen muss, dass diese Patienten nicht von der MMT profitieren können, da unklar bleibt, ob das Ausmaß des ungünstigen Kos tenverlauf ohne MMT höher gewesen wäre.…”
unclassified